Strengthening the Pancasila Student Profile in the Implementation of Merdeka Belajar for Elementary School-Aged Children in Malaysia: Penguatan Profil Pelajar Pancasila dalam Implementasi Merdeka Belajar pada Anak Usia Sekolah Dasar di Malaysia - Khatimah, Khusnul; Amin, Khoirul; Rachman, Dzul (Wadah Inovasi Indonesia, 2024)
Education plays a central role in shaping the character and civilization of a dignified nation. In Indonesia, the role of elementary schools is crucial as the foundational stage in forming students' identity and character. One of the key components of the Merdeka Belajar (Freedom to Learn) policy is strengthening the Profil Pelajar Pancasila (Pancasila Student Profile). Through this initiative, the values embedded in the Pancasila Student Profile—such as mutual cooperation (gotong royong), diversity (kebinekaan), independence (kemandirian), and critical thinking—are successfully introduced and cultivated in students through hands-on and reflective activities. This effort also demonstrates that even abroad, Pancasila-based character education can still be instilled and developed through adaptive and collaborative learning.